Perspectives on differing health outcomes by city: accounting for Glasgow’s excess mortality - Fraser SD; George S (Dove Medical Press, 2015)
Simon DS Fraser, Steve George Academic Unit of Primary Care and Population Sciences, Faculty of Medicine, University of Southampton, Southampton, Hampshire, UKAbstract: Several health outcomes (including mortality) and health-related behaviors are known to be worse in Scotland than in comparable areas of Europe and the United Kingdom. Within Scotland, Greater Glasgow (in West Central Scotland) experiences disproportionately poorer outcomes independent of measurable variation in socioeconomic status and other important determinants. Many reasons for this have been proposed, particularly related to deprivation, inequalities, and variation in health behaviors. The use of models (such as the application of Bradford Hill’s viewpoints on causality to the different hypotheses) has provided useful insights on potentially causal mechanisms, with health behaviors and inequalities likely to represent the strongest individual candidates. This review describes the evolution of our understanding of Glasgow’s excess mortality, summarizes some of the key work in this area, and provides some suggestions for future areas of exploration. In the context of demographic change, the experience in Glasgow is an important example of the complexity that frequently lies behind observed variations in health outcomes within and between populations. A comprehensive explanation of Glasgow’s excess mortality may continue to remain elusive, but is likely to lie in a complex and difficult-to-measure interplay of health determinants acting at different levels in society throughout the life course. Lessons learned from the detailed examination of different potentially causative determinants in Scotland may provide useful methodological insights that may be applied in other settings. Ongoing efforts to unravel the causal mechanisms are needed to inform public health efforts to reduce health inequalities and improve outcomes in Scotland.Keywords: Glasgow effect, mortality, inequalities, determinants